O Ginásio Escola Normal Virgílio Távora e sua contribuição para a formação de docentes no Maciço de Baturité/CE - Araújo, Maria das Graças de (2018)
The present Doctorate thesis is a case study contemplating the history of the Virgilio Tavora Primary School and Teacher Training College, also known as GVT, and its contribution to education in the region known as Massif of Baturité/CE. The GVT was a philanthropic organization located in the city of Aracoiaba/CE. It was founded by Salomão Alves de Moura Brasil, in 1958, being maintained by the Aracoiaba Educators Association until 2004, when it ceased its activities. In 1960 it started with Junior High School, but from 1964 it began to offer the Teacher Training Course. The Additional Studies were incorporated in 1974. Our intent is to comprehend the history of GVT and its contribution to the training of the primary school teachers in the aforementioned region of Massif of Baturité. This study seeks to verify how the Teacher Training Course and the Additional Studies Programme were developed, emphasizing the changes that occurred in the period in which the referred courses operated. In doing so, it will pursue – following the narratives of teachers who studied in that institution –, to identify, not only how their training processes happened, but also the foundations of the educational practices developed by the GVT. And thus, to analyze the contribution of the school for the lives and professional activity of the teachers who studied there. Bibliographical researches, consultations both in the school archives and documents from another institutions and interviews with former students of the school were carried out; we also have used photos to illustrate the events. The collected data was analyzed based on the cross-referencing of the information contained in the written and oral sources, considering the theoretical postulates that underpinned the investigation. It is well known that the GVT contributed to the training of teachers in Aracoiaba and in all the region of the Massif of Baturité, in regard to its pioneering and educational practices, among other aspects. The bygone Teacher Training Courses and Additional Studies Programme were considered by those educators who participated in them to be effective. To conclude, it was noticed that the very process of teacher training influences the professional practice – even though oscillating, according to the changes of time, between precariousness and efficacy, according to changes in time, influences professional practice.